Implementation Of Extreme Programming In The Develop-ment Of Class And Reservation Management Application At Fitness Centers - Sihombing, Denny Jean Cross (SEAN Institute, 2024)
This research investigates the implementation of Extreme Programming (XP) in developing a class management and reservation application in fitness centers. The issues under scrutiny include identifying precise system requirements, applying XP principles in the design and imple-mentation phases of the application, and evaluating application per-formance through comprehensive testing. The research methodology encompasses system requirement analysis, architectural planning, pro-totype development, functionality testing, and performance evaluation. The findings indicate that implementing XP effectively enhances appli-cation quality, user interface responsiveness, and user satisfaction. The contribution of this research lies in providing practical guidance for software developers in applying XP for efficient and high-quality ap-plication development, as well as enriching the literature on software development methodologies.